Values of White Blood Cell Count and C-Reactive Protein in Diagnosis of Acute Appendicitis - Khaled Elbaruni; Eman Abdulwahed; Mona Elwafi; Maram Eljrew; Atia, Ahmed (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objectives. Acute appendicitis is one of the most common surgical emergencies. Accurate diagnosis of acute appendicitis is based on careful history, physical examination, and laboratory investigation. The purpose of this study is to investigate the value of white blood cells (WBC) and C-reactive protein (CRP) in the diagnosis of acute appendicitis. Methods. A retrospective analysis of 350 files of patients who underwent appendectomy was conducted. Selected files were those patients who were admitted to ALmasara clinic Tripoli Libya between Aug 2011 to July 2023, ages of patients ranged from 18 to 80 years. Statistical analysis was performed using SPSS version 26 software. A statistical procedure was implemented to compare the hematologic parameters in two groups (Males and Females) to determine if there was any significant difference between them. Means of WBC, Neutrophil, Lymphocyte and CRP were compared between two groups by an independent one-way analysis of variance (ANOVA). Results. This study consisted of 350 participants who were diagnosed with appendicitis. The results showed that about (69.4%) of appendicitis patients exhibited a high white blood cell count (leukocytosis). Slightly over half (52.6%) of the participants had an elevated neutrophil percentage (neutrophilia). Approximately (64.3%) of the appendicitis patients had decreased lymphocyte percentage (lymphopenia). In relation to CRP values, the study showed that most participants (76.5%) had positive CRP results. Conclusion. Individuals with appendicitis have higher levels of leukocytes, neutrophils, and C-reactive protein, and decreased lymphocyte counts. Elevated WBC and CRP values together provide a better specificity and positive predictive value than individual markers. الخلفية والأهداف. يعد التهاب الزائدة الدودية الحاد أحد أكثر حالات الطوارئ الجراحية شيوعًا. يعتمد التشخيص الدقيق لالتهاب الزائدة الدودية الحاد على التاريخ الدقيق والفحص البدني والفحوصات المخبرية. الغرض من هذه الدراسة هو دراسة قيمة خلايا الدم البيضاء (WBC) والبروتين التفاعلي (CRP) في تشخيص التهاب الزائدة الدودية الحاد. طُرق الدراسة. تم إجراء تحليل بأثر رجعي لملفات 350 من المرضى الذين خضعوا لعملية استئصال الزائدة الدودية. الملفات المختارة هي المرضى الذين تم إدخالهم إلى عيادة المسرة طرابلس ليبيا في الفترة ما بين أغسطس 2011 إلى يوليو 2023، وتراوحت أعمار المرضى من 18 إلى 80 عامًا. تم إجراء التحليل الإحصائي باستخدام برنامج SPSS الإصدار 26. تم تنفيذ إجراء إحصائي لمقارنة المتغيرات الدموية في مجموعتين (الذكور والإناث) لتحديد ما إذا كان هناك أي فرق كبير بينهما. وتمت مقارنة وسائل WBC، العدلات، الخلايا الليمفاوية وCRP بين مجموعتين من خلال تحليل التباين المستقل في اتجاه واحد (ANOVA). النتائج. تكونت هذه الدراسة من 350 مشاركًا تم تشخيص إصابتهم بالتهاب الزائدة الدودية. أظهرت النتائج أن حوالي (69.4%) من مرضى التهاب الزائدة الدودية أظهروا ارتفاعاً في عدد خلايا الدم البيضاء (كثرة الكريات البيضاء). كان لدى ما يزيد قليلاً عن النصف (52.6%) من المشاركين نسبة مرتفعة من العدلات (العدلات). حوالي (64.3%) من مرضى التهاب الزائدة الدودية كان لديهم نقص في نسبة الخلايا الليمفاوية (قلة الليمفاويات). فيما يتعلق بقيم CRP، أظهرت الدراسة أن معظم المشاركين (76.5٪) لديهم نتائج إيجابية لـ CRP. الخاتمة. الأفراد الذين يعانون من التهاب الزائدة الدودية لديهم مستويات أعلى من الكريات البيض، والعدلات، والبروتين التفاعلي سي، وانخفاض عدد الخلايا الليمفاوية. توفر قيم WBC وCRP المرتفعة معًا خصوصية أفضل وقيمة تنبؤية إيجابية مقارنة بالعلامات الفردية.